Supply chain risk assessment and management toolkit - Wiegel, Jennifer Rebecca; Siles, Pablo; Claros Trujillo, Luisa María; Angulo, Jessenia; Charry, Andres; Mai Vu, Nguyen Phuong; Nguyen, Thuy Thanh; Talsma, Tiffany; Celi, Giacomo (2023)
The Supply Chain Risk Assessment and Management Toolkit, developed by the Alliance of Bioversity International and CIAT in collaboration with FMO and Mercon Coffee Group, has the objective of helping companies assess the risks of engaging with or endorsing unlawful/unethical practices in their agricultural supply chains, and defining adequate measures to prevent, minimize and mitigate their impacts. The toolkit groups risks in three major Areas: Labor, Human Rights, and Environment, which are further disaggregated in Sub-Areas and Components. The analysis is carried out at a Macro and Micro level, providing companies a contextualized, nuanced, and granular understanding of the challenges they (may) face, which will guide the development of tailored risk management strategies.